Association of Sodium-Glucose Cotransporter 2 (SGLT2) Inhibitor Use With Cardiovascular and Renal Outcomes in Type 2 Diabetes Mellitus Patients With Stabilized Acute Myocardial Infarction: A Propensity Score Matching Study - Chang, Ting-Yung; Lu, Chi-Ting; Huang, Hsin-Lei; Chou, Ruey-Hsing; Chang, Chun-Chin; Liu, Chung-Te; Huang, Po-Hsun; Lin, Shing-Jong (Frontiers in Cardiovascular Medicine, 2022)
Background - Coronary artery disease (CAD) is one of the leading causes of morbidity and mortality in patients with type 2 diabetes mellitus (T2DM), who are at a greater risk of acute myocardial infarction (AMI) and sudden cardiac death. Sodium-glucose cotransporter 2 (SGLT2) inhibitors have been shown to reduce cardiovascular events and mortality in T2DM patients with a risk of cardiovascular disease. This study aimed to investigate the effect of SGLT2 inhibitor use on the adverse cardiovascular and renal outcomes in T2DM patients with AMI. Methods - A total of 1,268 patients admitted to the Coronary Care Unit due to AMI were retrospectively screened.Patients taking SGLT2 inhibitors before or during the index AMI hospitalization were assigned as group 1. Patients who never received SGLT2 inhibitors were assigned as group 2. Patients in groups 1 and 2 were matched in a 1:2 ratio, and 198 T2DM patients with stabilized AMI were retrospectively enrolled for the final analysis. Results - With a mean follow-up period of 23.5 ± 15.7 months, 3 (4.5%) patients in group 1 and 22 (16.7%) patients in group 2 experienced rehospitalization for acute coronary syndrome (ACS), while 1 (1.5%) patient in group 1 and 7 (5.3%) patients in group 2 suffered sudden cardiac death. The Kaplan–Meier curves demonstrated that the patients in group 1 had a lower risk of adverse cardiovascular outcomes. According to the multivariate analysis, the baseline estimated glomerular filtration rate (eGFR) (P = 0.008, 95% CI: 0.944–0.991) and the use of SGLT2 inhibitors (P = 0.039, 95% CI: 0.116–0.947) were both independent predictors of adverse cardiovascular outcomes. On the other hand, the use of SGLT2 inhibitors was not associated with adverse renal outcomes. Conclusion – In T2DM patients with stabilized AMI, the use of SGLT2 inhibitors was associated with a lower risk of adverse cardiovascular outcomes. In addition, the baseline renal function was also an independent predictor of adverse cardiovascular outcomes.